Repeatability of magnetic resonance fingerprinting T1 and T2 estimates assessed using the ISMRM/NIST MRI system phantom - Jiang, Yun; Ma, Dan; Keenan, Kathryn E.; Stupic, Karl F.; Gulani, Vikas; Griswold, Mark A. (Magnetic resonance in medicine, 2017)
Purpose The purpose of this study was to evaluate accuracy and repeatability of T1 and T2 estimates of a MR fingerprinting (MRF) method using the ISMRM/NIST MRI system phantom. Methods The ISMRM/NIST MRI system phantom contains multiple compartments with standardized T1, T2, and proton density values. Conventional inversion‐recovery spin echo and spin echo methods were used to characterize the T1 and T2 values in the phantom. The phantom was scanned using the MRF‐FISP method over 34 consecutive days. The mean T1 and T2 values were compared with the values from the spin echo methods. The repeatability was characterized as the coefficient of variation of the measurements over 34 days. Results T1 and T2 values from MRF‐FISP over 34 days showed a strong linear correlation with the measurements from the spin echo methods (R2 = 0.999 for T1; R2 = 0.996 for T2). The MRF estimates over the wide ranges of T1 and T2 values have less than 5% variation, except for the shortest T2 relaxation times where the method still maintains less than 8% variation. Conclusion MRF measurements of T1 and T2 are highly repeatable over time and across wide ranges of T1 and T2 values. Magn Reson Med 78:1452–1457, 2017. © 2016 International Society for Magnetic Resonance in Medicine.